2000
DOI: 10.1096/fj.99-0959com
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal fatty acid binding protein is not essential for dietary fat absorption in mice

Abstract: The intestinal fatty acid binding protein (I-FABP) belongs to a family of 15 kDa clamshell-like proteins that are found in many different tissues. So far, nine types have been identified. Their primary structures are highly conserved between species but somewhat less so among the different types. The function of these proteins, many of which are highly expressed, is not well understood. Their ability to bind lipid ligands suggests a role in lipid metabolism, but direct evidence for this idea is still lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
0
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 19 publications
10
137
0
7
Order By: Relevance
“…There are two main FABPs in the small intestine, the intestinal type (I-FABP) and the liver-type (L-FABP). Previous reports indicated that I-FABP was not essential for fatty acid absorption (Vassileva et al, 2000) and that L-FABP exhibited a higher affinity for unsaturated LCFA than I-FABP (Richieri et al, 1994). In addition, L-FABP had the ability to increase fatty acid uptake (Prows et al, 1995), so we examined the changes in L-FABP mRNA expression in jejunum under changing dietary conditions.…”
Section: Discussionmentioning
confidence: 97%
“…There are two main FABPs in the small intestine, the intestinal type (I-FABP) and the liver-type (L-FABP). Previous reports indicated that I-FABP was not essential for fatty acid absorption (Vassileva et al, 2000) and that L-FABP exhibited a higher affinity for unsaturated LCFA than I-FABP (Richieri et al, 1994). In addition, L-FABP had the ability to increase fatty acid uptake (Prows et al, 1995), so we examined the changes in L-FABP mRNA expression in jejunum under changing dietary conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The crystal structure of human heart FABP (HFABP) containing an oleic acid ligand (1HMS.pdb). The protein structure is similar for all the FABPs and shows the β-barrel domain and the N-terminal helixturn-helix motif (37).…”
Section: Referencesmentioning
confidence: 96%
“…Differentiated enterocytes of the proximal small intestine express high levels of two FABPs, LFABP and the intestine-specific form, intestinal FABP (IFABP; FABP2). The distal small intestine expresses a third member of the FABP family, ileal bile acid-binding protein (ILBP; FABP6) (47,48). There appears to be no compensatory up-regulation of LFABP upon ablation of IFABP or vice versa, again indicating unique functional roles.…”
Section: Tissue-specific Fabp Functionsmentioning
confidence: 99%